2022
DOI: 10.1177/00916471221102550
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception of COVID-19, Religiosity, and Subjective Well-Being in Emerging Adults: The Mediating Role of Meaning-Making and Perceived Stress

Abstract: The pressured experienced due to COVID-19 for young people has become clearly visible in the domain of well-being. Although the psychological effects of the COVID-19 pandemic on emerging adults have been examined, little is known about the role played by risk perception and religiosity for their well-being. In addition, the mediating effects of meaning-making and perceived stress still need to be investigated. A total of 316 emerging adults (143 males and 173 females) participated in the present study. Using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Risk perception is a subjective judgment made by residents on the risk characteristics and severity of ride-pool travel [31]. When studying the relationship between travel and risk, Roehl et al proposed seven types of risks that may exist in travel [32].…”
Section: Risk Perception Scalementioning
confidence: 99%
“…Risk perception is a subjective judgment made by residents on the risk characteristics and severity of ride-pool travel [31]. When studying the relationship between travel and risk, Roehl et al proposed seven types of risks that may exist in travel [32].…”
Section: Risk Perception Scalementioning
confidence: 99%
“…Successfully creating meaning in uncertain and distressing times has been shown to lead to positive outcomes. Data from a sample of young Polish adults showed that meaning-making explained relationships between religiosity and perceived stress, life satisfaction and positive and negative affect (Krok et al, 2021(Krok et al, , 2023. Similarly, undergraduate students in the USA who were enrolled in research-based classes were able to maintain interest in the class despite virtual learning adaptations but only if they were able to make meaningful connections between the learning activities and their personal or career goals (Wang et al, 2020).…”
Section: Meaning-making During Covidmentioning
confidence: 99%
“…RPC is the affective and cognitive reflection of COVID-19 events and is perceived as the key driver of those mental and behavioral outcomes [2,3]. The reduction of well-being is frequently explored due to risk perception recently [4,5]. For instance, Krok and Zarzycka examined 226 southern polish health care workers using the questionnaire method.…”
Section: Introductionmentioning
confidence: 99%